Leptospira borgpetersenii Leucine-Rich Repeat Proteins Provide Strong Protective Efficacy as Novel Leptospiral Vaccine Candidates - Siriwan Prapong; Yada Tansiri; Tepyuda Sritrakul; Sineenat Sripattanakul; Aukkrimapann Sopitthummakhun; Gerd Katzenmeier; Chin-Lin Hsieh; Sean P. McDonough; Teerasak Prapong; Yung-Fu Chang (My University, 2022)
Leucine-rich repeat (LRR) proteins are advocated for being assessed in vaccine development. Leptospiral LRR proteins were identified recently in silico from the genome of Leptospira borgpetersenii serogroup Sejroe, the seroprevalence of leptospiral infections of cattle in Thailand. Two LRR recombinant proteins, rKU_Sej_LRR_2012M (2012) and rhKU_Sej_LRR_2271 (2271), containing predicted immunogenic epitopes, were investigated for their cross-protective efficacies in an acute leptospirosis model with heterologous Leptospira serovar Pomona, though, strains from serogroup Sejroe are host-adapted to bovine, leading to chronic disease. Since serovar Pomona is frequently reported as seropositive in cattle, buffaloes, pigs, and dogs in Thailand and causes acute and severe leptospirosis in cattle by incidental infection, the serogroup Sejroe LRR proteins were evaluated for their cross-protective immunity. The protective efficacies were 37.5%, 50.0%, and 75.0% based on the survival rate for the control, 2012, and 2271 groups, respectively. Sera from 2012-immunized hamsters showed weak bactericidal action compared to sera from 2271-immunized hamsters (p < 0.05). Therefore, bacterial tissue clearances, inflammatory responses, and humoral and cell-mediated immune (HMI and CMI) responses were evaluated only in 2271-immunized hamsters challenged with virulent L. interrogans serovar Pomona. The 2271 protein induced prompt humoral immune responses (p < 0.05) and leptospiral tissue clearance, reducing tissue inflammation in immunized hamsters. In addition, protein 2271 and its immunogenic peptides stimulated splenocyte lymphoproliferation and stimulated both HMI and CMI responses by activating Th1 and Th2 cytokine gene expression in vaccinated hamsters. Our data suggest that the immunogenic potential renders rhKU_Sej_LRR_2271 protein a promising candidate for the development of a novel cross-protective vaccine against animal leptospirosis.
Keywords: Leptospira interrogans; Leptospirosis research and findings